Exploring the Narrative Experience of Somali-Djiboutian Youth In and About Ottawa Public Schools - Farah, Hassan K. (Université d'Ottawa / University of Ottawa, 2011)
This study is an examination into the schooling experiences of an immigrant group of students of Somali-Djiboutian origin who graduated from public schools in Northeastern Ontario over the last two to three years. I show that racialized, visible minority young people face unique barriers and struggles as the intersecting effects of race and class influence their experiences (see also, Desai and Subramanian, 2000; Ibrahim, 2005; Kilbride, Anisef, Baichman-Anisef & Khattar, 2000; Rummens, 2003). Their racialized experiences are central to this study, with special emphasis on how this experience either opens or closes social, material or academic possibilities. Through qualitative research based on interviews, the study explores how young people are able to articulate and negotiate their identities while going through the schooling process. To further investigate this process, I have used an antiracist framework that employs a structural analysis of racism and recognize the contradictory consciousness and consequences that are often involved in the struggle for justice in an inherently competitive and unjust educational system (Henry et & al., 2000; Bannerji, 2000; Dei, 2006, 2005). Through their narratives, participants are able to break the silence and speak out with the aim of illuminating the tensions and contradictions between their experiences in relation to educational policy and actual school practices. The use of interviews reveals perspectives of the participants’ dilemmas that have taken place within the formal and informal educational setting. The research participants were limited to eight graduates from high school in the last two to three years. It is hoped that the completed project may be used by members of the Somali-Djiboutian community to lobby for educational change.